Object identification in simultanagnosia: When wholes are not the sum of their parts. - Riddoch, M; Humphreys, G (2004)
We examined object identification in two simultanagnosic patients, ES and GK. We show that the patients tended to identify animate objects more accurately than inanimate objects (Experiments 1 and 4). The patients also showed relatively good identification of objects that could be recognised from their global shape, but not objects whose recognition depended on their internal detail (Experiment 2). Indeed, the presence of local segmentation cues disrupted global identification (Experiment 3). Identification was aided, though, by the presence of surface colour and texture (Experiment 4). We suggest that the patients could derive global representations of objects that served to recognise animate items. In contrast, they were impaired at coding parts-based representations for the identification of inanimate objects.